2003
DOI: 10.1002/jtr.449
|View full text |Cite
|
Sign up to set email alerts
|

Economic aspects and the Summer Olympics: a review of related research

Abstract: As the Summer Olympics are growing with larger media coverage and sponsorship, host cities have started to attach great importance to the tourism and other likely economic effects that occur by staging such a special event. As a result, a number of studies have been conducted to consider the various economic implications on the hosts. This paper examines and evaluates methods and assumptions used by the economic studies. It also compares ex-ante models and forecasts with the ex-post approach. The aim is to imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
142
0
15

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(157 citation statements)
references
References 12 publications
0
142
0
15
Order By: Relevance
“…Their direct impacts will mainly be in the Lower Lea Valley, and there will also be a general impact on leisure facilities more widely. Evidence from previous Olympics suggests that the mediumterm impact on tourism may be modest, particularly for a city with an established reputation as a tourism destination (Kasimati 2003). The regional impacts will be highly polarised in and around London, and in sites such as Weymouth which will host the sailing events.…”
Section: The Growing Internationalisation Of Tourismmentioning
confidence: 99%
“…Their direct impacts will mainly be in the Lower Lea Valley, and there will also be a general impact on leisure facilities more widely. Evidence from previous Olympics suggests that the mediumterm impact on tourism may be modest, particularly for a city with an established reputation as a tourism destination (Kasimati 2003). The regional impacts will be highly polarised in and around London, and in sites such as Weymouth which will host the sailing events.…”
Section: The Growing Internationalisation Of Tourismmentioning
confidence: 99%
“…In general, impacts can be grouped into three categories: economic (e.g. Kasimati 2003); socio-cultural (e.g. Fredline & Faulkner 2000); and environmental (e.g.…”
Section: Overview Of the Literaturementioning
confidence: 99%
“…A survey found that hosting the 1996 Atlanta Games boosted employment by as much as 17 per cent in selected counties in Georgia (Hotchkiss et al, 2003). Evangelia Kasimati (2003) reviews the economic impact literature and finds that the Games result in economic growth, increased tourism, and additional employment. One report estimates that the net economic impact on the host city averages from $4 billion to $5 billion (McKay and Plumb, 2001).…”
Section: The Games As Urban Makeovermentioning
confidence: 99%